Surgical Site Infections - A Hospital Havoc: Retrospective Study of Surgical Site Infections in Tertiary Health Care Centre in North East India - Singh, V; W V Lyngdoh, A B Khyriem,; Lyngdoh, C J (International Journal of Innovative Research in Medical Science, 2018)
Objectives - Surgical site infections (SSI) has turn out to be a major problem even in hospital with most modern facilities and standard protocols of pre -operative preparation and antibiotic prophylaxis. Objective of this study is to know the prevalence of surgical site infection among the postoperative patients and to identify the relationship between SSI and etiological pathogens along with their antimicrobial susceptibility at North Eastern Indira Gandhi Regional Institute of Health and Medical Sciences (NEIGRIHMS), Shillong. Methods - A retrospective case study conducted at NEIGRIHMS, among patients admitted to the surgical departments during the period between January 1st and December 31st 2016. Swabs from the surgical sites were collected under sterile conditions and standard bacteriological tests were performed for identification and appropriate statistical methods were employed to look for association between SSI and etiological pathogens. Results - Out of the 1284 samples included in the study, 192 samples showed evidence of SSI yielding an infection rate of 14.9%. The most commonly isolated bacteria were: Escherichia coli, Acinetobacter baumanii and Staphylococcus aureus, of the gram negative isolates 6.2% were multidrug resistant of which 19% were carbapenem resistant. Conclusion - SSI with multiple drug resistance strains and polymicrobial etiology reflects therapeutic failure. The outcome of the SSI surveillance in our hospital revealed that in order to decrease the incidence of SSI we would have to: a) incorporate a proper antibiotic stewardship b) conduct periodic surveillance to keep a check on SSI d) educate medical staffs regarding the prevention of surgical site infection.